Health seeking behavior and associated factors among individuals with cough in Yiwu, China: a population-based study - Xiaoyan Sun; Shuying Luo; Lingqiao Lou; Hang Cheng; Zhen Ye; Jianwei Jia; Yina Wei; Jingbo Tao; Hanqing He (BMC, 2021)
Abstract Background Previous studies have shown that a certain proportion of the population did not seek medical treatment after coughing, and understanding the potential reasons is crucial for disease prevention and control. Method A population-based study was conducted with the probability proportional to population size sampling in Yiwu, Zhejiang, China. A total of 5855 individuals aged ≥15 years lived in Yiwu for more than 6 months were included. All participants completed a laptop-based questionnaire to collect detailed information by a face-to-face interview. Characteristics of individuals were described by categories of health seeking behavior using frequency and percentage. Univariate and multivariate logistic regression analyses were performed to estimate the associations of social-demographic and cough characteristics with health seeking behavior. Results 19.3% (1129/5855) of participants had a cough in the past month, 40% (452/1129) had sought medical treatment. Of these, 26.5% (120/452) chose hospitals at county level or above. Individuals aged ≥65 years old (OR = 2.25, 95% CI: 1.23, 4.12), female (OR = 1.57, 95% CI: 1.21, 2.06), living in rural areas (OR = 1.30, 95% CI: 1.003, 1.69), persistent cough for 3-8 weeks (OR = 2.91, 95% CI: 1.72, 4.92) and with more accompanying symptoms (P trend < 0.001) were more likely to seek medical treatment, but those coughed for > 8 weeks were not (p > 0.5). Female (OR = 0.33, 95% CI: 0.21, 0.54) and people living in rural areas (OR = 0.57, 95% CI: 0.36, 0.92) were less likely to choose hospitals at county level or above while the higher educated were more likely to (OR = 3.29, 95% CI: 1.35, 8.02). Those who coughed for more than 2 weeks were more likely to choose hospitals at or above the county level. But the number of accompanying symptoms does not show any significant relationship with the choice of medical facility. Conclusion The present study found that age, sex, living areas and features of cough were associated with health seeking behavior. It is worth noting that those who coughed for too long (e.g. > 8 weeks) were less likely to seek medical treatment. Targeted measures should be developed based on the key factors found in this study to guide persons to seek medical treatment more scientifically.